Design proposal for masonry infill walls subject to seismic actions - Leite, João; Lourenço, Paulo B.; Mendes, N. (Applied sciences, 2022)
Several factors influence the behaviour of masonry infilled frames, which have been the subject of previous research with moderate success. The new generation of European design standards imposes the need to prevent the brittle collapse of infills and makes the structural engineer accountable for this requirement, yet it fails to provide sufficient information for masonry infill design. The present study aimed to compare experimental results with the provisions of the standard for the computation of the demand and capacity of infilled frames. Three reinforced concrete buildings with different infill solutions were constructed at a 1:1.5 scale. The infill walls were tested until collapse, or severe damage, using the shake table of the National Laboratory for Civil Engineering, Portugal, and their response was measured using accelerometers attached to the walls. The European normative standard provides results close to the experimental ones as far as demand and capacity are concerned. Based on the experiments, two design proposals for infill walls are presented here, one for the definition of the natural frequency of the infills, and another for a reduction factor to account for the presence of openings in the out-of-plane capacity of infills.